2019
DOI: 10.1152/ajplung.00197.2019
|View full text |Cite
|
Sign up to set email alerts
|

NOTCH signaling promotes the survival of irradiated basal airway stem cells

Abstract: Radiation-induced lung injury to normal airway epithelium is a frequent side-effect and dose-limiting factor in radiotherapy of tumors in the thoracic cavity. NOTCH signaling plays key roles in self-renewal and differentiation of upper airway basal lung stem cells during development, and the NOTCH pathway is frequently deregulated in lung cancer. In preclinical lung cancer models, NOTCH inhibition was shown to improve the radiotherapy response by targeting tumor stem cells, but the effects in combination with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 56 publications
1
15
0
Order By: Relevance
“…In the lung, recent work from Stripp and colleagues showed that radiation reduces the in vitro colonyforming ability of epithelial progenitor cells from distal airways (27,28). We recently demonstrated that NOTCH signaling promotes the survival of irradiated P63 þ basal stem cells through activation of the 53BP1/DNA damage response pathway (29). Whether this also impacts on the protective response of FLASH is not known.…”
Section: Discussionmentioning
confidence: 99%
“…In the lung, recent work from Stripp and colleagues showed that radiation reduces the in vitro colonyforming ability of epithelial progenitor cells from distal airways (27,28). We recently demonstrated that NOTCH signaling promotes the survival of irradiated P63 þ basal stem cells through activation of the 53BP1/DNA damage response pathway (29). Whether this also impacts on the protective response of FLASH is not known.…”
Section: Discussionmentioning
confidence: 99%
“…It is worth mentioning that combining Notch inhibitors with radiotherapy had quite contrasting consequences for airway epithelium regeneration in experimental works. Radiation damages the DNA of progenitor cells, and Notch signaling inactivation increases the phosphorylation of ATM and CHK2 and alters DNA damage response, but it could result both in decreased and improved renewal capacity of basal stem cells in different conditions [608,609].…”
Section: Nsclcmentioning
confidence: 99%
“…Indeed, this system better resembles the in vivo structure of the lung and allows the coculture with different cell types such as tumor cells, fibroblasts, or immune cells. For instance, lung SC response to radiation was studied by Giuranno et al using this model [ 8 , 10 ]. Inhibition of the Notch SC pathway was shown to increase lung SC self-renewal upon IR, contributing to a more intact epithelium as assessed in a completely differentiated setting [ 8 ].…”
Section: Models To Study Sc Response To Radiationmentioning
confidence: 99%
“…Inhibition of the Notch SC pathway was shown to increase lung SC self-renewal upon IR, contributing to a more intact epithelium as assessed in a completely differentiated setting [ 8 ]. This effect was not observed in 2D models, which do not permit the culture of the differentiated cells, suggesting the contribution of the luminal cells to SC response to RT [ 10 ]. This indicates that the choice of the right model may be crucial for translating preclinical research findings to clinical practice.…”
Section: Models To Study Sc Response To Radiationmentioning
confidence: 99%
See 1 more Smart Citation